An Empirical Study of Intention to Extend Work- Life after Retirement among Nurses and Midwives in Nigeria: Application of Theory of Planned Behaviour - Nasiru, Muhammad Anka; Md Dahlan, Nuarrual Hilal (Institute for Political and international Studies (IPIS) of Iran, 2021)
In Nigeria, a severe shortage of registered nurses (RNs) and Registered midwives (RMs) have made the management carefully propose a programme to extend professionals working lives after retirement. However, there is a shortage of knowledge regarding the intention and preparedness of the preceding health professionals to continue working even after they passed retirement age. This study's objective was to apply the theory of planned behaviour (TPB) to assess the intention and the actual preparation to elongate employment following retirement among the Nigerian nurses and midwives (RNs & RMs). This study employed a cross-sectional survey design as well as recruitment emails to collect 446 usable questionnaires from 45 years or older. The study’s result showed a significant positive association among attitude and intention to work following retirement (ß=0.38, t=3.81, p<0.00) and subjective norm (SN) and intention to work after retirement (ß=0.28, t= 2.56, p<0.01). Also, the study’s result shows perceived behavioural control (PBC) and intent to extend employment after retirement (ß=0.17, t=2.03, p<0.02) and between intent to work following retirement and actual preparation to take a job after retirement (ß=0.69, t=29.90, p<0.00). This study indicated that appreciating the key TPB variables associated with extending working life among the respondents leads to appropriate plan services to support the health professionals in functioning past their actual retirement age. Consequently, this study found that TPB is a crucial model that is a superior predictor of individuals' behaviours than other theories. The result derived from the above approach will help the Nigerian government improve policies that promote adequate healthcare services by retaining an experienced health professional workforce.